HETEROGENEITY OF A PLUME AXIS: BULK-ROCK GEOCHEMICAL EVIDENCE FROM PICRITES AND BASALTS IN THE EMEI LARGE IGNEOUS PROVINCE, SOUTHWEST CHINA - Zengqian H.; Jiren L.; Shengzhong L. (My University, 2006)
In order to document the chemical characteristics of sources of a continental flood basalt (CFB) and to understand its origin, we studied four typical picrite-basalt flows and three picritic intrusions in the Emeishan picrite-cluster field (5 × 104 km2 area), located in the southwestern part of the Emei large igneous province. Major and trace elements, and Sr-Nd-Pb isotopic compositions, are reported for picrites and associated basalts in the picrite-cluster field, regarded as the axial area of the Emei mantle plume. These rocks exhibit a range of MgO contents (4.2-27.2%), variable degrees of LREE enrichment (LaN/YbN = 2.7-29.0), and heterogeneous isotopic ratios εNd(t) = 4.84 to -4.00; initial 87Sr/86Sr = 0.7023-0.7064; 206Pb/204Pb = 18.034-20.641). Nd, Sr, and Pb isotopic covariations are similar to at least three groups of the picrites and basalts. Ontong Java-like lavas yielded low (87Sr/86Sr)i (<0.7045), high εNd(t) (>2.5), and the lowest (Ce/Yb)N (~4), La/Sm (~3), Th/Nb (~0.75), La/Nb (~0.85), and Ba/Nb (~8) ratios, suggesting a focus zone (FOZO)-like mantle source. Cook-Austral-like lavas have high 206Pb/204Pb (>19.0), low (87Sr/86Sr)i (<0.7045), and high Sm/Yb (>4), Nb/Y (>1) and Zr/Y (>8), similar to the HIMU component. Heard-like lavas yielded high (87Sr/86Sr)i (0.7044 ~ 0.7060), low εNd(t) (1.7 to -3.0), 206Pb/204Pb (18.75-18.03) and 208Pb/204Pb (37.8-39.0), and high (Ce/Yb)N (>10), Ba/Nb (>30), and Th/Nb (>0.1), which might be explained by mixing of picritic magmas from the plume with lamproitic melt from continental lithospheric mantle. Three samples outside the three groups have Sr-Nd isotopic signatures similar to EM I, and high Th/Nb (>0.2), La/Nb (>1.5), and low Nb/U (<25), suggesting a pelagic sediment source component. The picritic intrusives have low εNd(t) (0.32-0.59), intermediate (87Sr/86Sr)i (0.7037-0.7042) very high Th/Nb (0.11-0.20), and low Nb/U (<25), implying minor crustal assimilation. The trace elements and Sr-Nd-Pb isotope geochemistry of the Emei picrites and associated basalts reflect processes involving: (1) partial melting of a heterogeneous, eclogite-bearing source to produce picritic magmas; then (2) mixing with small amounts of melt from the continental lithospheric mantle; and (3) crustal assimilation during picritic magma ascent. The heterogeneity of this source is related to recycling of subducted oceanic crust and associated sediments into the deep upper mantle. Copyright © 2006 by V. H. Winston & Son, Inc. All rights reserved.